# |
ODE |
Mathematica |
Maple |
\[
{}x^{2}+3 \ln \left (y\right )-\frac {x y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (x y-x -y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 y^{3} y^{\prime } = \left (x +4 y \ln \left (y\right )\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \ln \left (x \right ) \ln \left (y\right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{{3}/{2}}+x^{2}+y^{2}+2 y \sqrt {x}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y \cos \left (x y\right )+x \cos \left (x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+x = 4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-6 x \,{\mathrm e}^{x -y}-1 = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x \right )+\cos \left (x \right )^{2}-\cos \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (6 y^{2}-x -1\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+\cos \left (x \right )\right ) y^{\prime }+\sin \left (x \right ) \left (\sin \left (x \right )+\sin \left (x \right ) \cos \left (x \right )-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +\sin \left (\frac {y}{x}\right )^{2} \left (-x y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{4} {\mathrm e}^{y}+2 x y^{3}+y+\left (x^{2} y^{4} {\mathrm e}^{y}-x^{2} y^{2}-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{3}-1+y^{2} y^{\prime } x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right ) a
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +\sin \left (x \right )+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+3 \cosh \left (x \right )+2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b x +c y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \cos \left (b x +c \right )+k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \sin \left (b x +c \right )+k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b \,{\mathrm e}^{k x}+c y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (x^{2}-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left ({\mathrm e}^{-x^{2}}+a y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} \left (a \,x^{3}+b y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \,x^{n} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \cos \left (x \right )+y \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\sin \left (x \right )}+y \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-y \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \csc \left (x \right )-y \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (2 \csc \left (2 x \right )+\cot \left (x \right )\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sec \left (x \right )-y \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \sin \left (x \right )+y \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\csc \left (x \right )+2 y \cot \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 \csc \left (x \right ) x \sec \left (x \right )^{2}-2 y \cot \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \cot \left (x \right )^{2} \cos \left (2 x \right )-2 y \csc \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 \csc \left (x \right ) x \left (\sin \left (x \right )^{3}+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 \csc \left (x \right ) x \left (1-\tan \left (x \right )^{2}+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) = \left (1-y\right ) \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )+\tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )-\tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sec \left (x \right )-\tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (2 x \right )+\tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (2 x \right )-\tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )+2 \tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2+2 \sec \left (2 x \right )+2 y \tan \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \csc \left (x \right )+3 \tan \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (a +\cos \left (\ln \left (x \right )\right )+\sin \left (\ln \left (x \right )\right )\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 \,{\mathrm e}^{2 x}-y \tanh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right ) f^{\prime }\left (x \right )+f^{\prime }\left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )+g \left (x \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+f \left (x \right )^{2} = f^{\prime }\left (x \right )+y^{2}
\] |
✗ |
✓ |
|
\[
{}y^{\prime }+1-x = y \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3-3 x +3 y+\left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -\left (x^{2}+1\right ) y+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (x^{3}+2\right )-\left (2 x^{2}-y\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x \left (-x^{3}+2\right )+\left (2 x^{2}-y\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )-\left (\sin \left (x \right )-y\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (2 x \right )+\left (\sin \left (2 x \right )+y\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )+x f \left (x \right ) y+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (3+x -4 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+4 x +9 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 a +3 b x +3 b y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b x +c y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \,x^{n -1}+b \,x^{2 n}+c y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \,x^{2}+b y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {a0} +\operatorname {a1} y+\operatorname {a2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )+a y+b y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1+a \left (x -y\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )+g \left (x \right ) y+y^{2} a
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = x y \left (3+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x -x^{3}+\left (2 x^{2}+1\right ) y-x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (2+x^{2} y-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +\left (1-2 x \right ) y-\left (1-x \right ) y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{n} \left (a +b y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \,x^{m}+b \,x^{n} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (a +b y \cos \left (k x \right )\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \left (2 \sec \left (x \right )^{2}-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 \csc \left (x \right ) = \left (3-\cot \left (x \right )\right ) y+y^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sec \left (x \right )+\left (-1+\sin \left (x \right )\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) \left (1-y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \left (a +b y+c y^{2}\right ) f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (a x +y\right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (a \,{\mathrm e}^{x}+y\right ) y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 a \left (y+2 x \right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (a +b y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \operatorname {a0} +\operatorname {a1} y+\operatorname {a2} y^{2}+\operatorname {a3} y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \left (1-x y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (a +b x y\right ) y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y \left (1+a x y^{2}\right ) = 0
\] |
✓ |
✓ |
|